A phylogeny for genus Capra based on extensive sampling of wild populations - Steve Jordan; Saeid Naderi; Hamid-Reza Rezaei; Gordon Luikart (PLoS ONE, 2025)
Among the most economically and ecologically important taxa are those with wild and domestic counterparts, such as the true goats (genus Capra ), that are distributed and used by humans world-wide. Such taxa often played roles in the spread of pastoralism, farming, and modern societies. To advance understanding of the Capra , a relatively recent radiation across Eurasia, we generated one of the most complete taxonomic datasets for this genus to date. It includes 4603 bp of DNA sequence data for 11 nuclear loci from a broad geographic distribution of Capra , including 52 wild and 10 domestic individuals from nine species and 21 countries. All wild species were sampled in the wild (not in captivity). Results support the monophyly of recognized IUCN (International Union for Conservation of Nature) taxa, C. ibex , C. nubiana , C. pyrenaica , and C . sibirica while offering little support for the monophyly of C. aegagrus , C . falconeri , C. hircus , C. caucasica , or C. cylindricornis . We confirm wild goats ( C. aegagrus ) are the likely sole ancestor of domestic goats. This study bolsters and confirms prior studies, demonstrating the usefulness of multiple independent nuclear genes and widespread sampling of wild and domestic individuals for studies of taxa important to humans.